Effects of LIF on neuromuscular junction formation in Co-cultures of rat spinal cord explant and human muscle - Marš, Tomaž (Array, 2008)
Summary: Leukemia inhibitory factor (LIF) is a multifunctional cytokine important in nerve and muscle cells development and maintenance. The effects of LIF on the formation of neuromuscular junction (NMJ) have not been studied directly, that is why we employed the in vitro model of human muscle cell cultures innervated by rat embryonic motor neurons. In this model, several aspects of neuromuscular junction formation can be studied. The aim of the study was to test if LIF promotes the formation of functional NMJ. The effects of LIF on neuronal outgrowth, acetylcholine receptor accumulation and the formation of functional contacts were tested. Co-cultures treated with higher concentrations of LIF have increased neuronal outgrowth, higher number of acetylcholine receptor clusters and finally at later stages also a higher degree of functional innervation. LIF positively promotes the formation of neuromuscular junction in specific concentration range. Effects appeared to be stronger at later stages of NMJ formation in our co-cultures. The model of in vitro innervated human muscle cell can be a useful experimental system for testing toxic and therapeutic effects of substances on the formation and development of neuromuscular systems at cellular level